Efektivitas Promosi Kesehatan 5S terhadap Pengetahuan, Sikap dan Praktik 5S Pekerja di PT Charoen Pokhand Semarang - Donardo Yudha Arthanto; Eko Hartini (VISIKES: Jurnal Kesehatan Masyarakat, 2016)
PT. Charoen Pokphand Indonesia Semarang is agro-business enterprise engaged in the field of fodder. PT. Charoen Pokphand realized that implementation of 5S has an important role in the conduct of operations and the company’s workers. To make the 5S program is implemented by employees, it should be disseminated through various media, such as media. This research  aims to analyze the effectiveness of 5S health promotion to knowledge, attitudes, and practices of 5S on PT. Charoen Pokphand employees.This was experimental study with quasi experimental design one group pretest-posttest design on 50 respondents. Data was analyzed by by Wilcoxon test.The results showed significant increase of knowledge, attitude and practice between pre and post test, before and after 5S health promotion intervention. After employee exposed to  booklets and poster, the improvement of knowledge was 33.3%, attitude was 14.75%, and practice was 16.46%.The 5S health promotion through media booklet and poster were effective for improving knowledge, attitudes, and practices of employee in the implementation of 5S in the processing area of PT. Charoen Pokphand Indonesia. The resercher suggests  corporate officers to educate employee on  the implementation of 5S through safety talk media,every morning before work.Keyword: 5S, health promotion, knowledge, attitude, practice